2022
DOI: 10.1021/acscatal.2c01044
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Photocatalytic Two-Electron Shuttle between Paired Redox Sites on Halide Perovskite Nanocrystals

Abstract: Perovskite semiconductors as advanced solar energy-converting materials are promising catalysts for photoredox organic synthesis. Despite the high concentration of charge carriers generated on the perovskite surface, efficient utilization of these nonequilibrium and shambolic energetic carriers to trigger a chemical reaction remains a hot and challenging subject. Here, we report a photon-mediated electron shuttle between paired redox sites on perovskite nanocrystals for the reformation of highly stable carbon–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…Visible-light-driven photocatalysis has been a very promising strategy for solar-to-chemical energy conversion. , To improve the light-to-energy conversion efficiency in visible-light photocatalysis, extensive efforts are applied to design and develop new heterogeneous photocatalysts. Plasmonic metal nanoparticles (NPs) as emerging heterogeneous photocatalysts have aroused considerable interest , because of their large absorption cross sections in the visible region. As their most prominent feature, the metallic NPs have strong interactions with visible light to generate coherent oscillations of free electrons within the NPs, which is called localized surface plasmon resonance (LSPR). , Via a nonradiative decay channel, excited surface plasmons in the metallic NPs would decay into energetic hot carriers (electron–hole pairs), where the high energy electrons are above the Fermi Level, while the hot holes are below it.…”
Section: Introductionmentioning
confidence: 99%
“…Visible-light-driven photocatalysis has been a very promising strategy for solar-to-chemical energy conversion. , To improve the light-to-energy conversion efficiency in visible-light photocatalysis, extensive efforts are applied to design and develop new heterogeneous photocatalysts. Plasmonic metal nanoparticles (NPs) as emerging heterogeneous photocatalysts have aroused considerable interest , because of their large absorption cross sections in the visible region. As their most prominent feature, the metallic NPs have strong interactions with visible light to generate coherent oscillations of free electrons within the NPs, which is called localized surface plasmon resonance (LSPR). , Via a nonradiative decay channel, excited surface plasmons in the metallic NPs would decay into energetic hot carriers (electron–hole pairs), where the high energy electrons are above the Fermi Level, while the hot holes are below it.…”
Section: Introductionmentioning
confidence: 99%
“…228 CsPbX 3 perovskites were also used as photoredox catalysts for aromatic substitutions in organic synthesis. 229 Some of the practical applications for perovskites overlap with those given in section 5.5 for hexaaluminates, and additional background information on certain topics is provided there.…”
Section: Stabilization Of Transition Aluminas By Dopantsmentioning
confidence: 99%
“…Recently, it was reported that the photoactive phase of CsPbI 3 could be stabilized in a metal–organic framework (MOF) glass . CsPbX 3 perovskites were also used as photoredox catalysts for aromatic substitutions in organic synthesis …”
Section: Lanthanum Monoaluminate (Lma)mentioning
confidence: 99%
“…The CsPbBr 3 perovskite nanocrystals (NCs) have been explored as photocatalysts in organic synthesis in recent years. CsPbBr 3 perovskite NCs are a type of metal halide perovskite material that has been extensively studied in the field of optoelectronics, particularly in the development of solar cells and light-emitting diodes (LEDs). , The CsPbBr 3 perovskite NCs are a promising new class of photocatalysts that have the potential to significantly improve the efficiency and selectivity of organic reactions . However, their low stability and limited efficiency have been a major challenge to their practical use. , …”
mentioning
confidence: 99%